Weathering the storm: Analyzing the impact of extreme climate events on energy consumption across 141 countries - Chun Kai Leung; Jeremy Ko; Chunlan Guo (Innovation and Green Development)
The paper examines the effects of extreme weather events—specifically floods, extreme temperatures, bushfires, and droughts—on per capita energy consumption across 141 countries from 1990 to 2023. While existing research often aggregates various natural disasters or focuses on localized contexts, this study offers a comprehensive global perspective, analyzing how distinct types of extreme weather impact energy consumption patterns. Employing a fixed-effects panel regression model, the findings reveal that floods correlate with increased energy consumption, particularly in developing countries, whereas droughts are associated with decreased energy use. In contrast, extreme temperatures and bushfires do not exhibit a statistically significant impact on energy consumption. Robustness checks using alternative models, such as the Tobit model and two-stage least squares regression, confirm the reliability of these results. The analysis suggests that floods escalate energy demand due to the extensive recovery and mitigation efforts required, while droughts diminish consumption through their detrimental effects on agriculture, industry, and hydropower production. These findings hold significant implications for energy policy and climate resilience, underscoring the necessity to enhance the adaptability of energy systems, improve energy efficiency, and extend support to developing nations facing climatic stressors. This study contributes to the understanding of how extreme weather events shape energy dynamics, providing insights for the formulation of targeted policies aimed at ensuring sustainable development in the face of climate challenges.